A Geodemographic View of the Accessibility of Selected Outpatient Services in Czechia - Kateřina Maláková (Frontiers Media S.A., 2022)
Objectives: Although people use health services throughout their lives, there are important differences in timing, location, and frequency of utilization. The aim of this article is to identify and explain these differences in terms of healthcare accessibility.Methods: Outpatient health services-diabetology, cardiology, and psychiatry-are analysed using anonymized data from the General Health Insurance Company (GHIC) in Czechia for 2019. Healthcare utilization is studied in relation to selected geodemographic characteristics-patient's age, sex, place of permanent residence, and location of healthcare provision.Results: The analysis found significant differences in the utilization of the selected health services in terms of age, sex, and size of the patient's municipality of residence. Generally, men tended to travel outside their municipality for healthcare more than women. Young patients were more likely (and also further) to travel outside their municipality for healthcare than older patients.Conclusion: The reasons for this were the location of the health service provider (mostly concentrated in local/regional centres), the patient's ability and willingness to travel for healthcare, and differences in the patient's permanent and ordinary place of residence.